Impact of Diastolic Vessel Restriction on Quality of Life in Symptomatic Myocardial Bridging Patients Treated With Surgical Unroofing: Preoperative Assessments With Intravascular Ultrasound and Coronary Computed Tomography Angiography. (October 2021) - Hashikata, Takehiro; Honda, Yasuhiro; Wang, Hanjay; Pargaonkar, Vedant S.; Nishi, Takeshi; Hollak, M. Brooke; Rogers, Ian S.; Nieman, Koen; Yock, Paul G.; Fitzgerald, Peter J.; Schnittger, Ingela; Boyd, Jack H.; et al.
Abstract : Background: Despite optimal medical therapy, a myocardial bridge (MB) can cause life-limiting symptoms in a subset of patients. While surgical unroofing has been shown to improve MB-derived refractory angina, diagnostic indices of clinical symptoms and predictors of improvement following surgery are yet to be elucidated. Methods: To identify determinants of preoperative symptoms and their improvement following the surgery, preoperative intravascular ultrasound (IVUS) and coronary computed tomography angiography were evaluated in 111 patients with symptomatic MB who underwent surgical unroofing. The primary outcome was the Seattle Angina Questionnaire summary score (the average of physical limitation, angina frequency, and quality of life scores). In addition to standard anatomic variables of an MB, degrees of extrinsic vessel restriction at end-diastole and end-systole were evaluated by IVUS using the ratio of measured vessel area and interpolated reference at the maximum compression site. The diastolic restriction was also evaluated by coronary computed tomography angiography as the maximum lumen area stenosis within the MB segment. Results: Even during diastole, IVUS revealed vessel restriction in 87% of the patients. Among the variables evaluated, vessel restriction was the strongest parameter correlating with the preoperative Seattle Angina Questionnaire summary score, particularly when assessed in diastole ( P <0.0001 in IVUS, P =0.006 in coronary computed tomography angiography). The diastolic restriction by IVUS also showed a weak, but significant correlation with improvement in Seattle Angina Questionnaire summary score 6 months after surgery ( P =0.004). Conclusions: Restricted arterial relaxation in diastole, rather than the degree of systolic compression or extent of an MB, seems to be the primary determinant of clinical symptoms and improvement in quality of life following surgical unroofing. Abstract : Supplemental Digital Content is available in the text.